Effect of incorporation of lemongrass extract and lemongrass oil on the sensory, physico-chemical and textural profile of paneer - Joseph, Krupa; Rao, K Jayraj (Indian Journal of Dairy Science, 2019)
Paneer represents a variety of Indian soft cheese, highly nutritious and wholesome, used as a base material for the preparation of a large number of culinary dishes. Due to the ever growing demand of paneer by varied health conscious consumers, it is necessary to develop new varieties of paneer. Lemongrass is an aromatic perennial tall tropical grass and yields an aromatic oil with citral as its major component. This study evaluated the effect of addition of natural lemongrass flavor into paneer, as a flavouring agent. Lemongrass flavor was incorporated in either of the following three ways: i) cut and crushed leaves into milkÂ  @ 0, 2, 4 and 6% (w/v) orÂ  @ 20% (w/v) into the coagulant solution extracted by heat treatment; 2) Extraction of leaves in potable water followed by heat concentration and chilling for dipping purpose of paneer blocks; 3) Addition of lemongrass oil into milk as well as coagulant solution at various levels (0, 0.015, 0.02 and 0.025%). The samples with lemongrass extract as well as oil obtained satisfactory sensory scores. Paneer sample with the addition of cut lemongrass leaf (4% w/v) into milk, was selected as the optimized sample based on sensory acceptance. The textural and physico-chemical properties of paneer remained unaffected, with the exception of increase in acidity and decrease in pH, with increased level of addition of lemongrass into paneer. It is concluded from the present study, that lemongrass has improved the flavour and sensory attributes of paneer and holds the potential for development of value added dairy products.